ANALISIS BIAYA OPERASIONAL KENDARAAN AKIBAT KEMACETAN DI JEMBATAN BAROMBONG: ANALYSIS OF VEHICLE OPERATING COSTS DUE TO CONGESTION ON THE BAROMBONG BRIDGE - Tedemaking, Redemtus De Ferento Sili; Thioritz, Stevy; Mursalim (Jurnal Media Teknik Sipil, 2024)
Bridge facilities that are not functioning properly cause congestion during peak hours or certain time periods. The problem of congestion occurs when the flow of vehicles exceeds the road capacity on the bridge. the impact of this congestion can certainly increase vehicle operating costs for users of transportation facilities. This study discusses the effect of congestion on vehicle operating costs (BOK) at Barombong Bridge which aims to determine the increase in vehicle operating costs due to congestion, comparison of vehicle operating costs when traffic volumes are high and low and comparison of vehicle operating costs based on the level of service. This research was conducted by surveying data on traffic volume, vehicle speed and road geometrics at the observation location. The calculations in this study used the method developed by the Department of Public Works in 2005 for non-fixed costs. The results of this study showed that the amount of BOK incurred due to congestion in the morning period was Rp.43,232.06/km and BOK in the afternoon period was Rp.43,593.02/km. Based on the volume of traffic, vehicle operating costs have increased significantly. In the morning period, BOK increased by Rp.3,292.85, while in the afternoon period, BOK increased by Rp.3,728.90/km. When referring to the level of service increase of F and B, the BOK in the north direction in the morning period was obtained at Rp.2,143.586/km and in the afternoon period in the south direction at Rp.2,807.129/km. This shows that the BOK increases along with the increase in the degree of saturation.